PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI PRODUK BUNDLING DAN CROSS- SELLING PADA PROGRAM âTEBUS MURAHâ UNTUK QUICK-COMMERCE PT.X - Muhammad Iqbal, Fahmi
PT. X is a quick commerce company implementing a hyperlocal strategy focused on providing concentrated services within specific geographical boundaries. PT. X currently has twenty-five dark store locations to serve their customers. PT. X's customer satisfaction strategy includes offering discounts on bundled products, both for single-type products (wholesale) and product pair bundling. Additionally, PT. X currently has a cross-selling program named "Tebus Murah" that appears on the customer's checkout menu. However, the decision-making process for product bundling and cross-selling lack a solid foundation. Nevertheless, PT. X plans to select products for the "Tebus Murah" program based on their popularity. The design of the Decision Support System (DSS) in this study will be based on the market basket analysis (MBA) model with multi-dimensional association rule mining using the Apriori algorithm, considering the time range as input. The DSS designed in this study will accommodate location and time range inputs to be analyzed. The designed MBA model can accommodate the determination of products for single-product bundling, cross-product